2000
DOI: 10.4049/jimmunol.165.5.2677
|View full text |Cite
|
Sign up to set email alerts
|

The Chemokine Macrophage-Inflammatory Protein-1α and Its Receptor CCR1 Control Pulmonary Inflammation and Antiviral Host Defense in Paramyxovirus Infection

Abstract: In this work, we explore the responses of specific gene-deleted mice to infection with the paramyxovirus pneumonia virus of mice (PVM). We have shown previously that infection of wild type mice with PVM results in pulmonary neutrophilia and eosinophilia accompanied by local production of macrophage-inflammatory protein-1α (MIP-1α). Here we examine the role of MIP-1α in the pathogenesis of this disease using mice deficient in MIP-1α or its receptor, CCR1. The inflammatory response to PVM in MIP-1α-deficient mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
136
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(146 citation statements)
references
References 51 publications
6
136
3
Order By: Relevance
“…Similar to findings from the mouse model of influenza virus [26] we found that the chemokine, MIP-1α (CCL3), is crucial for granulocyte recruitment in response to PVM infection [23]. Specifically, MIP-1α gene-deleted mice are readily infected with PVM, although 10 5 -fold fewer granulocytes are recruited to the lung tissue in response to the identical initial inoculum.…”
Section: Mip-1α (Ccl3) Is a Crucial Component Of The Virus-induced Insupporting
confidence: 70%
See 1 more Smart Citation
“…Similar to findings from the mouse model of influenza virus [26] we found that the chemokine, MIP-1α (CCL3), is crucial for granulocyte recruitment in response to PVM infection [23]. Specifically, MIP-1α gene-deleted mice are readily infected with PVM, although 10 5 -fold fewer granulocytes are recruited to the lung tissue in response to the identical initial inoculum.…”
Section: Mip-1α (Ccl3) Is a Crucial Component Of The Virus-induced Insupporting
confidence: 70%
“…We initially recapitulated the aforementioned findings of Horsfall and colleagues and reported robust virus replication in situ (to titers as > 10 8 pfu/gm lung tissue), progressing to marked morbidity (hunching, fur ruffling), weight loss, and mortality, in our case in response to a minimal virus inoculum of the highly pathogenic strain PVM J3666 [22,23]. We have localized immunoreactive PVM to the bronchiolar epithelium [24], in a distribution similar to what has been observed for RSV in human post-mortem specimens [25; Figure 3].…”
Section: Inflammatory Responses and Disease Severitymentioning
confidence: 88%
“…This redundancy might be important for the maintenance of normal host defense and immune functions. Consistent with this hypothesis, CCR1 -/-mice exhibited elevated CCL3 levels compared to wild-type mice in response to the paramyxovirus pneumonia virus infection [13]. However, it is also possible that the compensatory production of chemokines may elicit an aberrant inflammatory cell migration, resulting in tissue injuries.…”
Section: Discussionmentioning
confidence: 71%
“…CCR1/CCL3 interactions has been reported to inhibit neutrophil recruitment in some experimental models [10][11][12][13]. Moreover, CCR1 is expressed on mast cells, and induces mast cell migration through interaction with CCL5 [14].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies using CCR1-deficient mice have documented its role for neutrophil migration in the defense of certain infectious organisms such as Toxoplasma gondii, Paramyxovirus, and Aspergillus fumigatus (15,20,21). In the context of progressive fibrotic disease states, a recent study reported the effects of a neutralizing antibody against murine CCR1 in the bleomycin-induced pulmonary fibrosis model (22).…”
Section: Ccr1 Is Required For Leukocyte Infiltration After Uuomentioning
confidence: 99%